> 数学 >
先化简在求值.(X^2+2X分之X-2-X^2+4X+4分之X-1)除X+2分之X-4.其中X^2+2X...
先化简在求值.(X^2+2X分之X-2-X^2+4X+4分之X-1)除X+2分之X-4.其中X^2+2X-1=0.
人气:215 ℃ 时间:2020-05-29 09:51:24
解答
原式={[(x-2)/(x²+2x)]-[(x-1)/(x²+4x+4)]}÷[(x-4)/(x+2)]
={(x-2)/[x(x+2)]-[(x-1)/(x+2)²]}×[(x+2)/(x-4)]
=(x-2)/[x(x+2)]×[(x+2)/(x-4)]-[(x-1)/(x+2)²]×[(x+2)/(x-4)]
=(x-2)/[x(x-4)]-(x-1)/[(x+2)(x-4)]
=[(x-2)(x+2)]/[x(x+2)(x-4)]-[x(x-1)]/[x(x+2)(x-4)]
=[(x-2)(x+2)-x(x-1)]/[x(x+2)(x-4)]
=(x²-4-x²+x)/[x(x+2)(x-4)]
=(x-4)/[x(x+2)(x-4)]
=1/[x(x+2)
=1/(x²+2x)
因为x²+2x-1=0
所以x²+2x=1
所以
原式=1/1=1
推荐
猜你喜欢
© 2024 79432.Com All Rights Reserved.
电脑版|手机版